Palliative Management with Ultrasound Guided Percutaneous Pericardial Lavage for Cow with Pericarditis - A case Report - Venkatesan, M.; Selvaraj, P.; Saravanan, M.; Veeraselvam, M.; Yogeshpriya, S.; Jayalakshmi, K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This work is licensed under the Creative Commons Attribution International License (http:// creativecommons.org/licenses /by/4.0/P), which permits unrestricted use, distribution and reproduction in any medium, provided the original work is properly cited. Copyright @: 2019 by authors and SVSBT. Traumatic reticulopericarditis is a very frequently occurring, high morbid and mortality syndrome affecting bovines in large animal practice. It is quite common in delta districts of Tamil Nadu. For early intervention and economic loss minimization, appropriate diagnostic and prognostic testing is essential. Ultrasound guided, percutaneous pericardiocentesis is the non-invasive technique and helped in therapeutic management and prognostication of traumatic reticulopericarditis. This case documented the successful utility of the palliative therapy.